PUBLISHING OF LITHUANIAN DIGITAL SERIALS (1996–2011) - ŠARLAUSKIENĖ, LINA (Knygotyra, 2012)
The paper deals with publishing the Lithuanian digital serials in the terms of book science. A comparative analysis of publishing digital serials in a ten-year period in Lithuania has been made, and publishing tendencies of these publications are presented. The research data have been obtained by a longitudinal analysis of the Lithuanian digital serials since 1996 by the methods of information search, document analysis and publishers’ survey. Electronic serials have been analyzed according to the dynamics of publishing, type of publications, publisher, periodicity, purpose, topic, economic models, formal perfection and design. The research data of 2012 are compared with the data of analogous research performed in 2001. In the economic, content and form dimensions, the development of publishing the Lithuanian digital serials, started ten years ago, at present is a successfully developing field of professional activity comprising publications of various types, periodicity, and topics.
Keywords: ...